Chemical constituents and toxicity effects of selected botanical extracts on Spodoptera litura fabricius (lepidoptera: noctuidae) - Loh, Siew Fan (2011)
Sustainable and environmental friendly control methods such as botanical insecticides are urgently needed to reduce the negative impact caused by chemical insecticides. Experiments were conducted to search for potential plant extracts against the armyworm, Spodoptera litura (F.). Solvents extracts and essential oils from black pepper fruits (Piper nigrum L.), kaffir lime (Citrus hystrix DC) and lantana leaves (Lantana camara L.) were used to test the toxicity and their effect on larvae development. Dried plant materials were used for solvent extraction while essential oils were extracted from the fresh plant materials. Solvent extractions were conducted using hexane, chloroform and acetone to elute compounds of different polarities. Essential oils were obtained by hydrodistillation and their compositions were analyzed by GC-MS. A total of 39 compounds were detected in the essential oil fraction of P. nigrum fresh fruits, which contained high percentage of monoterpenes compounds. A total of 29 compounds were detected in the essential oil fraction of kaffir lime leaves, which contained high percentage of oxygenated monoterpenes while a total of 40 compounds were identified in lantana oil which contained high number of sesquiterpenes and oxygenated sesquiterpenes. Plant extracts and essential oils were applied by topical bioassay to the uniform weighted second instar larvae. Different doses were tested on the larvae and the mortality was recorded at 24h and 48h after treatment. Data were evaluated through Probit Analysis to determine the LD50. Among the three plants tested, highest mortality was recorded in black pepper treated colony. Results showed that the toxicities decreased followed by P. nigrum hexane extract, P. nigrum acetone extract, leaf oil of L. camara, leaf oil of C. hystrix and P. nigrum chloroform extract. All of the solvent extracts of C. hystrix and L. camara leaves shown non toxic to the larvae. Essential oil of Citrus hystrix and hexane extract of Piper nigrum were used to test their efficacy in suppressing the larvae development by topical bioassay. Larvae mortality, larvae head capsules, larvae weight gained, percentage of pupation, pupae weight, malformed pupae, adult emergence and sex ratio were recorded. Antifeedant activity of the C. hystrix oil and P. nigrum extracts were evaluated through leaf dip bioassay. Feeding behaviour was recorded at 24h and 48h after treatment. From the investigation, both of the plant extracts showed effects against the larvae development and pupae formation. Hexane extract of P. nigrum showed outstanding results especially in pupae mortality and adult emergence. Total development growth index (TDGI) of C. hystrix and P. nigrum treatments were relatively lower as compared to control treatment. C. hystrix essential oil had higher repellency activity against the S. litura larvae as compared to P. nigrum.